New system - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
A study commissioned by CTA on setting up an integrated information system on agricultural research in West and Central Africa was completed in December 1998. It will serve as a basis for intensive information exchange and for defining future...